Answer:
Step-by-step explanation: just did it on apex
The pairs of triangles appear to be congruent are Triangles 1 and 4, Triangles 1 and 3 and Triangles 3 and 4, that is option B, option C and option E. This can be obtained by understanding the concept of congruence.
Which are the required pairs?Congruent triangles have same size and shape.Corresponding sides and angles are equal. Two congruent triangles can overlap perfectly.In the question, Triangle 2 is larger than the other triangles.
Triangle 1, Triangle 3 and Triangle 4 appears to have the same size and shape.
Thus Triangle 1, Triangle 3 and Triangle 4 appears to be congruent to each other.
Hence the pairs of triangles appear to be congruent are Triangles 1 and 4, Triangles 1 and 3 and Triangles 3 and 4, that is option B, option C and option E.
Learn more about congruence of triangles here:
brainly.com/question/4207242
#SPJ2
Find all complex numbers z satisfying the equation {z+1}/{z-1} = i.
9 points and brainiest: please answer!
Answer:
Step-by-step explanation:
{z+1}/{z-1} = i.
z+1 = i (z-1)
z+1 =iz -i
z - iz = -1 -i
z ( 1 -i) = - 1 -i
z = (- 1 - i ) /(1-i) = - (1+i)/(1-i)
z = - (1+i)(1+i)/(1-i)(1+i)
z = - (1+2i +i²)/ ( 1²-i²).........i² = -1
z =-2i/2
z = - i (one solution)
All the complex numbers z satisfying the equation {z+1}/{z-1} = i is z = -i.
What are Complex Numbers?Complex numbers are numbers which are of the form [tex]a + ib[/tex], where a and b are real numbers and i is the imaginary number called iota whose value is [tex]i^2[/tex]= -1.
Given equation is,
(z + 1) / (z - 1) = i
Multiplying both sides by (z - 1),
z + 1 = i (z - 1)
Let z = (a + bi)
Substituting,
(a + bi + 1) = i (a + bi - 1)
(a + bi + 1) - i (a + bi - 1) = 0
a + bi + 1 - (ai + b(i)² - i) = 0
a + bi + 1 - ai - b(i)² + i = 0
Now i² = -1
a + bi + 1 - ai + b + i = 0
Combining the like terms,
(bi - ai + i) + (a + 1 + b) = 0
i (b - a + 1) + (a + b + 1) = 0
Left hand side is a complex number.
A complex number is a + bi = 0, when a = 0 and b = 0.
So, we get,
(b - a + 1) = 0 and (a + b + 1) = 0
b - a = -1 and a + b = -1
So, combining,
a + b = b - a
a + a = b - b
2a = 0
a = 0
Substituting,
b = -1
So the complex number, z = a + bi = -i
Hence the complex number z = -i.
Learn more about Complex Numbers here :
https://brainly.com/question/20566728
#SPJ3
A translation moves point V(-2,3) to V’(2,7). Which are true statements about the translation?
Answer:
The translation is right 4 units and up 4 units
Step-by-step explanation:
we know that
The rule of the translation of the point V to V' is equal to
(x,y) ----> (x+4,y+4)
That means ----> The translation is right 4 units and up 4 units
Verify
V(-2,3) -----> V'(-2+4,3+4)
V(-2,3) -----> V'(2,7)
Is correct
The true statement is: The transformation is a vertical translation. (Statement 3)
Let's analyze each statement:
1. The point moves two units up and four units to the right.
- This statement is incorrect. The point moves four units up, not two units up.
2. The transformation rule is (x, y) → (x + 0, y + 4).
- This statement is incorrect. The transformation rule should be (x, y) → (x, y + 4) because the point moves vertically by adding 4 to the y-coordinate.
3. The transformation is a vertical translation.
- This statement is correct. The point moves vertically, changing only the y-coordinate.
4. The image is four units to the right of the pre-image.
- This statement is incorrect. The image is at the same x-coordinate as the pre-image (-2), so it's not four units to the right.
5. The translation can be described as (x, y) → (x - 2, y + 7).
- This statement is incorrect. The translation rule should be (x, y) → (x, y + 4) because the point only moves vertically.
Complete question:A translation moves point V(-2, 3) to V prime (-2, 7). Which of the following statements are true about the translation?
1. The point moves two units up and four units to the right.
2. The transformation rule is (x, y) → (x + 0, y + 4).
3. The transformation is a vertical translation.
4. The image is four units to the right of the pre-image.
5. The translation can be described as (x, y) → (x - 2, y + 7).
Expand. Your answer should be a polynomial in standard form. (b^2+5)(−b^2+7)=
(b^2+5)(−b^2+7)
Use the FOIL METHOD to expand.
-b^4 + 7b^2 - 5b^2 + 35
-b^4 + 2b^2 + 35
Did you follow?
Standard form (b^2+5)(−b^2+7) polynomial is = -b⁴+2b²+35
What are polynomials?A polynomial expression is an expression that can be built from constants and symbols.Polynomials are algebraic expressions that comprise exponents which can be added, subtracted, or multiplied. Polynomials are of different types. Monomial- Linear equations (A monomial is a polynomial with one term)Binomia l- quadratic equation (A binomial is a polynomial with two, unlike terms).
Using FOIL METHOD to expand.
(b²+5)(−b²+7)
=(b²+5)(7-b²)
=7b²-b⁴+35-5b²
=2b²-b⁴+35
= -b⁴+2b²+35
Learn more about polynomial here:-https://brainly.com/question/2833285
#SPJ2
This graph represents the function (see picture) a= ___ b= ___
Answer:
a=1, b=-12
Step-by-step explanation:
This is a rational function with a hole at x=3 and a vertical asymptote at x=-4.
The denominator of this rational function must be:
[tex](x - 3)(x + 4)[/tex]
When we expand using the distributive property, we get:
[tex] {x}^{2} + 4x -3 x - 12[/tex]
This simplifies to
[tex] {x}^{2} + x - 12[/tex]
Therefore the graphed rational function is:
[tex]f(x) = \frac{ {x}^{2} - 4x + 3 }{ {x}^{2} + x - 12 } [/tex]
Comparing this to
[tex]f(x) = \frac{ {x}^{2} - 4x + 3 }{ {x}^{2} +a x + b} [/tex]
We have
[tex]a = 1[/tex]
and
[tex]b = - 12[/tex]
Use the formula P=21+2w to find the width of a rectangle when the length is 18cm and perimeter is 48 ..
Answer:
w=6
Step-by-step explanation:
P=2(L)+2(w)
48= 2(18)+2w
48=36+2w
12=2w
w=6
checking;
48= 2(18)+2(6)
48= 36+12
48= 48
Solve for x.
3ln(x-4)=9
Answer:
[tex]x=e^3+4[/tex] (exact)
x = 24.0855 (rounded)
Step-by-step explanation:
We need to remember 3 rules:
1. ln means log_e (ln is log base e)
2. [tex]a^b=x\\SameAS\\log_ax=b[/tex]
3. [tex]aLogx=Logx^a[/tex]
Now we can write the equation as:
[tex]3Ln(x-4)=9\\3Log_e(x-4)=9\\Log_e(x-4)^3=9[/tex]
Now, we can convert it to exponential and solve:
[tex]Log_e(x-4)^3=9\\(x-4)^3=e^9\\\sqrt[3]{(x-4)^3}=\sqrt[3]{e^9} \\ x-4=e^3\\x=e^3+4[/tex]
This is the exact value of x, in 4 decimal places (by using calculator), it would be
x = 24.0855
Answer the equation below:
16-2t=5t+9
Answer:
t = 1
Step-by-step explanation:
Given
16 - 2t = 5t + 9 ( subtract 5t from both sides )
16 - 7t = 9 ( subtract 16 from both sides )
- 7t = - 7 ( divide both sides by - 7 )
t = 1
Answer:
2.43
Step-by-step explanation:
16-2t=5t+2t
16-9=5t+2t
17÷7=7t
t=2.43
help!
estimate
5609 divided 7
answers:
0.8
8
80
800
Answer:
D) 800
Step-by-step explanation:
5609/7 = 801.285
rounding to the nearest would be 800.
Anything below a 5 will go to the lower anything above a 5 will go higher:
ex: 804 would round nearest to 800
807 would round nearest to 810
Lana was trying to collect 3 pounds of cans to recycle.If she collects 1/4 of a pound each day,how many days will it take to collect 3 pounds?
Answer:
the answer is 12 days
Step-by-step explanation:
3×4=12
If a data set has more extremely large data values, the distribution is said to be __________________.
A. skewed right
B. negatively skewed
C. positively skewed
D. symmetric
Answer:
C. positively skewed
Step-by-step explanation:
If a data set has more extremely large data values, the distribution is said to be positively skewed.
Have a great day!
A data set with more extremely large data values is said to be skewed right or positively skewed. This describes a distribution where the tail on the right side is extended due to a few high extreme values.
Explanation:If a data set has more extremely large data values, the distribution is said to be skewed right or positively skewed. This occurs because the tail of the distribution on the right-hand side is longer or more drawn out compared to the left-hand side.
In a right-skewed distribution, the mean is typically larger than the median, and the mode lies to the left of the median. This asymmetry indicates a larger number of lower values and a few extreme higher values in the data set. For example, if we have a data set with the histogram showing a longer tail on the right, it suggests there are some very large values stretching the scale, resulting in a skewed right distribution.
You are balancing the checking account for your new lawn-care business. Based on the check register below, how much money is in the account?
Correct. We need a balance in order to answer the question.
Answer:
the rest of the question but the answer is $555.37
Step-by-step explanation:
simplify e^ln3x please
[tex]\bf \textit{Logarithm Cancellation Rules} \\\\ log_a a^x = x\qquad \qquad \stackrel{\textit{we'll use this one}}{a^{log_a x}=x} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ e^{\ln(3x)}\implies e^{\log_e(3x)}\implies 3x[/tex]
Answer:
3x
Step-by-step explanation:
e^ln3x
We know that e and ln are inverses of each other, so when we take e to the power ln, they cancel
e^ ln 3x
3x
19. A right cone has a radius of 5 cm, an altitude of 12 cm, and a slant height of 13 cm. Find its volume.
A. 314.2 cm3
B. 942.5 cm3
C. 300 cm3
D. 64.1 cm3
Answer:
[tex]314.2cm^3[/tex]
Step-by-step explanation:
We use the formula below to find the volume:
[tex]\pi r^2\frac{h}{3}[/tex]
Note:
r represents the radiush represents the height of the coneSimplify:
[tex]\pi 5^2\frac{12}{3}[/tex]
Solve the exponent first, then multiply the fraction:
[tex]\pi 5^2\frac{12}{3} \\\\ 5^2 = 25\\\\ 12/3 = 4\\\\ 25 * 4 = 100\\\\ 100\pi = 314.159[/tex]
Round:
314.15 -> 314.2
Our answer would be [tex]314.2cm^3[/tex]
help plz
question 1:
a.)8
b.)-8
c.)32.5
d.)-32.5
question 2:
a.)+8
b.)-8
c.)+32.5
d.)-32.5
Answer:
Question 1: 8
Question 2: -32.5
Step-by-step explanation:
Laura gets paid 8 dollars an hour to baby sit
8x represents how much Laura gets paid by the hour.
Laura owes her friend 32.50
-32.50 represents the amount she owes her friend
Combine
y = 8x - 32.50
Answer
Question 1: 8
Question 2: -32.5
Answer:
y = 8x-32.50
Step-by-step explanation:
She makes 8 dollars an hour babysitting. She will work x hours
She makes 8x
She owes 32.50 to her friend. This will be subtracted because she owes it
The amount of money she has at the end, y, is given by
y =8x-32.50
Solve the system of linear operations
Answer:
[tex]\boxed{(-2,1)}[/tex]
Step-by-step explanation:
[tex]\left \{ {{5x+2y=-8} \atop {x+4y=2}} \right.[/tex]
I'll be solving this system of equations using the elimination method since the x and y values are neatly lined up.
I want to get a pair of x's or y's that cancel out, and it looks like the easiest way to start would be by multiplying the first equation by -2 (the y's will cancel).
I chose to multiply the first equation by -2 instead of multiplying the second equation by 5 because -2 is a smaller number and easier to multiply by.
[tex]-2\times(5x+2y=-8)[/tex]
Distribute -2 inside the parentheses. Now you've got:
[tex]\left \{ {{-10x-4y=16} \atop {x+4y=2}} \right.[/tex]
Add up the equations from top to bottom.
-10x plus x is -9x, the -4y and 4y cancel out, and 16 plus 2 is 18. Make this one single equation.
[tex]-9x=18[/tex]
Divide both sides by -9.
[tex]x=-2[/tex]
Substitute this value of x into the second equation (less to do with the x since it has no coefficient which means no multiplying).
[tex](-2)+4y=2[/tex]
Add 2 to both sides.
[tex]4y=4[/tex]
Divide both sides by 4.
[tex]y=1[/tex]
The final answer is [tex]x=-2, ~y=1[/tex].
if two points on a line are (4,6) and B (8,-8) the rise is..? and the run is..? so the slope of the line is ...?
Step-by-step explanation:
[tex]rise=y_2-y_1\\\\run=x_2-x_1\\\\slope=\dfrac{rise}{run}`\\\\\text{We have}\ (4,\ 6),\ (8,\ -8).\ \text{Substitute:}\\\\rise=-8-6=-14\\\\run=8-4=4\\\\slope=\dfrac{-14}{4}=-\dfrac{7}{2}[/tex]
The next model of a sports car will cost 14.6% less than the current model. The current model costs $38,000 . How much will the price decrease in dollars? What will be the price of the next model?
Answer:
Part 1) The price will decrease $5,548
Part 2) The price of the next model is $32,452
Step-by-step explanation:
Let
x ----> the price of the next model
we know that
The current model costs $38,000 -----> represent the 100%
step 1
To find the price decrease in dollars multiply the current model price by 14.6%
14.6%=14.6/100=0.146
so
0.146*($38,000)= $5,548
step 2
Find the price of the next model
To find the price of the next model subtract the price decrease from the price of the current model
so
x=$38,000-$5,548=$32,452
Using the diagram as marked, find the length
of HE if GE is the perpendicular bisector of HF.
HE = ??
HELP PLEASE!!
just a quick note, that triangle is misleading some, since the HG side of 6 units, shows longer than GE which is 8, and of course 8 > 6.
Since GE is a perpendicular bisector, that means the angle at G is 90°.
Check the picture below.
To find the length of HE, we utilize the properties of a perpendicular bisector and trigonometry. Knowing that GE halves HF into two equal parts, we calculate HF using trigonometric concepts, then halve it to find HE.
Explanation:In the question, it's mentioned that GE is a perpendicular bisector of HF. This means that GE bisects HF into two equal lengths. Therefore, the length of HE will be equivalent to half of the length of HF.
Since, HF can be calculated using trigonometry as mentioned. By definition, cose = x/h, so if we know the height 'h' and the angle, we can find 'x' which in this case would be HF, and subsequently HE would be HF/2.
Moreover, in trigonometry, the length of side opposite to the right angle in a right-angled triangle is calculated by the Pythagorean theorem, which states that in a right-angled triangle, the square of the length of the hypotenuse (the side opposite the right angle) is equal to the sum of the squares of the lengths of the other two sides. We use this to find out HF if other two sides are known.
Learn more about Triangle Geometry and Trigonometry here:https://brainly.com/question/14385261
#SPJ5
Suppose that y varies inversely with x. Use the information to find k, and then choose the equation of variation. x = 2.5 when y = 100.
Answer:
see explanation
Step-by-step explanation:
Given that y varies inversely as x then the equation relating them is
y = [tex]\frac{k}{x}[/tex] ← k is the constant of variation
To find k use the condition x = 2.5 when y = 100
k = yx = 100 × 2.5 = 250
y = [tex]\frac{250}{x}[/tex] ← equation of variation
The constant of variation (k) in the inverse relationship equation (y = k/x) can be determined by multiplying the x and y values provided. In this case, k = 250. Therefore, the equation of variation would be y = 250 / x.
Explanation:Given the inverse relationship where y varies inversely with x, it follows the general equation of y = k/x. This relationship is provided by the constant of variation (k). It can be determined by multiplying the given x and y values.
In this case, x = 2.5 when y = 100. We substitute these into our inverse relationship equation, yielding 100 = k/2.5. By multiplying both sides by 2.5, we are able to find that k = 250. Therefore, the equation of variation would be y = 250/x.
Learn more about Inverse Variation here:
https://brainly.com/question/26149612
#SPJ3
[tex]( - 7x + 1) - (4x + 5)[/tex]
Answer:
-11x-4 is the answer if the expression to simplify is (-7x+1)-(4x+5).
Step-by-step explanation:
We are first going to distribute to get rid of the ( ):
-7x+1-4x-5
Pair up like terms:
-7x-4x+1-5
Combine the like terms:
-11x-4
Triangle ABC has vertices A(0,0) B(6,8) and C(8,4). Which equation represents the perpendicular bisected of BC?
Answer:
[tex]y = \frac{1}{2}x+\frac{5}{2}[/tex]
Step-by-step explanation:
The perpendicular bisector of a line passes through the mid-point of the line and the product of slopes of the line and perpendicular bisector will be -1.
So,
[tex]Mid-point\ of\ BC = (\frac{6+8}{2}, \frac{8+4}{2})\\= (\frac{14}{2}, \frac{12}{2})\\= (7,6)[/tex]
The line will pass through (7,6)
Now,
[tex]Slope\ of\ BC = m_1 = \frac{y_2-y_1}{x_2-x_1} \\=\frac{4-8}{8-6}\\= \frac{-4}{2}\\= -2[/tex]
Let
m_2 be the slope of perpendicular bisector
So,
m_1*m_2 = -1
-2 * m_2 = -1
m_2 = -1/-2 = 1/2
The standard equation of line is:
y=mx+b
Where m is slope
So putting the value of slope and point to find the value of b
[tex]6 = \frac{1}{2}*7 +b\\ 6 = \frac{7}{2} + b\\b = 6 - \frac{7}{2}\\ b = \frac{12-7}{2}\\b = \frac{5}{2}\\So,\ the\ equation\ of\ perpendcular\ bisector\ of\ BC\ is:\\y = \frac{1}{2}x+\frac{5}{2}[/tex]
..
Which of the following modern movements led to new ways of studying and
thinking about the natural world?
O
A. The capitalist movement
B. The communist movement
O
C. The scientific revolution
O
D. The Industrial Revolution
Answer:
C. The scientific revolution
Step-by-step explanation:
The scientific revolution led to new ways of studying and thinking about the natural world.
The Scientific Revolution is the modern movement that led to new ways of studying and thinking about the natural world. It was characterized by advances in various fields of science, and marked a transformation in scientific thought and practice.
Explanation:Among the options provided, option C -- The Scientific Revolution -- represents the modern movement that led to new ways of studying and understanding the natural world. The Scientific Revolution, which took place during the 16th and 17th centuries, was characterized by significant advances in physics, astronomy, biology, human anatomy, and chemistry. It marked a crucial period of transformation in scientific thought and practice, with philosophers and scientists starting to challenge traditional beliefs about nature and the universe, leading to the adoption of the scientific method.
Learn more about Scientific Revolution here:
https://brainly.com/question/35070422
#SPJ2
What is 51/7 by 31/9 in simplest form
Answer:
51/7 = [tex]\frac7 {2}{7}[/tex] 31/9 = [tex]\frac3{4}{9}[/tex]
Step-by-step explanation: I hope this helps you!
Answer:
Step-by-step explanation:
51/7 = 7 2/7
31/9 = 3 4/9
Hope this helps!
Write the point slope form of an equation of the line through the points (-2,-3) and (-7,4) please answer
Answer:
see explanation
Step-by-step explanation:
The equation of a line in point- slope form is
y - b = m(x - a)
where m is the slope and (a, b) a point on the line
Calculate m using the slope formula
m = (y₂ - y₁ ) / (x₂ - x₁ )
with (x₁, y₁ ) = (- 2, - 3) and (x₂, y₂ ) = (- 7, 4)
m = [tex]\frac{4+3}{-7+2}[/tex] = [tex]\frac{7}{-5}[/tex] = - [tex]\frac{7}{5}[/tex]
We can use either of the 2 points for (a, b)
Using (a, b) = (- 7, 4), then
y - 4 = -[tex]\frac{7}{5}[/tex](x - (- 7)), that is
y - 4 = - [tex]\frac{7}{5}[/tex](x + 7) ← in point- slope form
What is the probability
Answer: Last Option
[tex]P=0.4125[/tex]
Step-by-step explanation:
In this case we have a uniform probability. In the graph the horizontal axis represents the possible values of the variable x and the vertical axis represents the probability P(x).
To calculate the probability that x is between 4.71 and 7.4 we calculate the area under the curve.
The horizontal length between 4.71 and 7.4 is:
[tex]7.4-4.1 = 3.3[/tex].
Then notice that the vertical length in this interval is 0.125.
Then the area of a rectangle is:
[tex]A = lw[/tex]
Where l is the length and w is the width.
In this case we have to:
[tex]l = 3.3[/tex]
[tex]w = 0.125[/tex]
So
[tex]P = A = 3.3 * 0.125[/tex]
[tex]P=0.4125[/tex]
How can one thirdx − 2 = one fourthx + 11 be set up as a system of equations?
Answer:
3y-x= -6
4y-x=44 ....
Step-by-step explanation:
Let y= 1/3x-2
Let y= 1/4x+11
Now we are required to arrange them in standard form.
So,
y= 1/3x-2
Combine the variable terms:
-1/3x+y=-2
Multiply both sides by 3
3(-1/3x+y)=3* -2
-x+3y= -6
3y-x= -6 ---------equation 1
y= 1/4x+11
Combine the variable terms:
-1/4x+y = 11
Multiply both sides by 4
4(-1/4x+y) = 4*11
-x+4y=44
4y-x=44 -----------------equation 2
Therefore the system of equations is:
3y-x= -6
4y-x=44 ....
Answer: Hello there!
we have that "one thirdx − 2 = one fourthx + 11"
this means (1/3)x - 2 = (1/4)x + 11
now, we also can write this as:
(1/3)x - 2 = y = (1/4)x + 11
and now we have a system of equations:
(1/3)x - 2 = y
(1/4)x + 11 = y
or
(1/4)x - y = -11
(1/3)x - y = 2
- An experiment consists of rolling two fair
number cubes. What is the probability
that the sum of the two numbers will be
47 Express your answer as a fraction in
simplest form.
Answer:
0
Step-by-step explanation:
Each time two cubes are rolled, the sum can be a number from 2 (rolling 1 and 1) to 12 (rolling 6 and 6). It is impossible to get a sum of more than 12, so there is zero probability of getting a sum of 47.
Answer: 0
What is the distance between zero and -53 on the number line?
Hello There!
the distance between 0 and -53 on a number line would be 53 spaces. This is because they are exactly 53 spaces away from each other.
the mathematical name of this quadrilateral
Answer:
Its a kite
Step-by-step explanation:
Answer:
kite
Step-by-step explanation:
try not to get it confused with a rhombus
If pentagon OPQRS is dilated by a scale factor of seven over four from the origin to create O'P'Q'R'S', what is the ordered pair of point Q'? If O negative 1, 2, at P negative 5, 3, at Q negative 3, negative 2, at R 2, 1, and at S 2, 5.
Answer:
The order pair of point Q' is (-21/4 , -7/2)
Step-by-step explanation:
* Lets explain the dilation
- A dilation is a transformation that changes the size of a figure.
- The figure can become larger or smaller, but the shape of the
figure does not change.
- The scale factor, measures how much the image will be larger
or smaller
- If the scale factor greater than 1, then the image will be larger
- If the scale factor between 0 and 1, then the image will be smaller
- The center of dilation is a fixed point in the plane about which all
points are expanded or contracted
* Lets solve the problem
- The pentagon OPQRS is dilated by a scale factor 7/4
- The center of dilation is the origin
- The image of the pentagon after the dilation is O'P'Q'R'S'
∵ The coordinates of the vertices of the pentagon OPQRS are
O (-1 , 2) , P (-5 , 3) , Q (-3 , -2) , R (2 , 1) , S (2 , 5)
- To find the image of each point after the dilation multiply each
coordinates of the points by the scale factor of dilation
∵ The scale factor is 7/4
∵ The coordinates of point Q are (-3 , -2)
∴ The image of point Q after dilation is (-3 × 7/4 , -2 × 7/4)
∴ The image of point Q after dilation is (-21/4 , -7/2)
∵ Q' is the image of Q
∴ Q' = (-21/4 , -7/2)
* The order pair of point Q' is (-21/4 , -7/2)
Answer:
The answer is (−5.25, −3.5)
Step-by-step explanation:
-3 times 7/4 is -5.25. -2 times 7/4 is -3.5.